Regulation of plasma glycero-lysophospholipid levels by lipoprotein metabolism. Issue 23 (3rd December 2019) - Kurano, Makoto; Kano, Kuniyuki; Hara, Masumi; Tsukamoto, Kazuhisa; Aoki, Junken; Yatomi, Yutaka
Abstract : Glycero-lysophospholipids, such as lysophosphatidic acids and lysophosphatidylserine, are gathering attention, since specific receptors have been identified. Most of these compounds have been proposed to be bound to albumin, while their associations with lipoproteins have not been fully elucidated. Therefore, in this study, we aimed to investigate the contents of glycero-lysophospholipids (lysophosphatidic acids, lysophosphatidylcholine, lysophosphatidylethanolamine, lysophosphatidylglycerol, lysophosphatidylinositol, and lysophosphatidylserine) on lipoproteins and the modulation of their metabolism by lipoprotein metabolism. We observed that moderate amounts of glycero-lysophospholipids, with the exception of lysophosphatidylserine, were distributed on the LDL and HDL fractions, and glycero-lysophospholipids that had bound to albumin were observed in lipoprotein fractions when they were co-incubated. The overexpression of cholesteryl ester transfer protein decreased the plasma levels of lysophosphatidylcholine, lysophosphatidylethanolamine, lysophosphatidylglycerol, and lysophosphatidylinositol and it increased their contents in apoB-containing lipoproteins, while it decreased their contents in HDL and lipoprotein-depleted fractions in mice. The overexpression of the LDL receptor (LDLr) decreased the plasma levels of lysophosphatidylcholine, lysophosphatidylethanolamine, lysophosphatidylglycerol, and lysophosphatidylinositol and decreased the contents of these compounds in the LDL, HDL, and lipoprotein-depleted fractions, while the knockdown of the LDLr increased them. These results suggest the potential importance of glycero-lysophospholipids in the pleiotropic effects of lipoproteins as well as the importance of lipoprotein metabolism in the regulation of glycero-lysophospholipids.